Preparation method of temperature-controllable fabric and application thereof in outdoor clothes

CN122918844APending Publication Date: 2026-10-16SHANGHAI GAOFAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611072382.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]目前多采用涂层整理法将PCM负载于织物表面,但普遍存在以下问题:一是整理剂与纤维之间缺乏牢固的化学键合,水洗后PCM易脱落,长效温控与耐水洗性难以兼顾;二是为提高负载量和附着力,往往采用高固含量涂层或致密交联网络,导致织物孔隙被堵塞,透气性和穿着舒适性显著下降;三是户外高强度使用中,涂层在反复弯折、摩擦作用下易出现粉化、开裂、剥落等问题,温控功能快速失效

Benefits of technology

本发明通过巯基改性β-环糊精包覆相变材料(SH-β-CD-PCM)与聚多巴胺改性碳纳米管(PDA-CNT)的协同作用,结合紫外光引发交联构建涂层主体网络与饱和蒸汽诱导优化涂层微结构的双重处理工艺,使相变材料牢固锚定于涂层网络,显著提高了面料的耐水洗性、耐磨性及户外高强度使用中的涂层稳定性。30次水洗后相变焓保持率可达82.2%;同时,剥离强度和耐磨性显著提升,耐磨次数达12500次,有效解决了户外高强度使用中涂层易剥落、易失效的问题。本发明制得的温控面料兼具长效温控、耐水洗及户外高强度耐用的优异性能,具备良好的产业化价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784515582597-000001
    Figure REF-OBJ-1784515582597-000001
  • Figure REF-OBJ-1784515582597-000002
    Figure REF-OBJ-1784515582597-000002
  • Figure REF-OBJ-1784515582597-000003
    Figure REF-OBJ-1784515582597-000003
Patent Text Reader

Abstract

The present application relates to the technical field of textile functional materials, in particular to a preparation method of temperature-controlling fabric and application thereof in outdoor clothes. A finishing liquid is prepared by dispersing thiol-modified beta-cyclodextrin coated phase change materials, polydopamine modified carbon nanotubes, vinyl silane coupling agent, photoinitiator and water-based polyurethane emulsion in water, a base cloth is dip-napped in the finishing liquid for two-dip-two-nap treatment, and then is sequentially subjected to pre-drying, ultraviolet crosslinking, saturated steam induction treatment, drying and setting, and cooling and winding to obtain the temperature-controlling fabric. The thiol-modified beta-cyclodextrin coated phase change materials and the polydopamine modified carbon nanotubes are synergistically used, and the dual treatment process of ultraviolet light-induced crosslinking to construct the main network of the coating and saturated steam induction to optimize the microstructure of the coating is combined, so that the phase change materials are firmly anchored in the coating network, and the prepared temperature-controlling fabric has excellent properties of long-acting temperature control, washing resistance and outdoor high-strength durability, and has good industrialization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile functional materials technology, specifically to a method for preparing a temperature-controlled fabric and its application in outdoor clothing. Background Technology

[0002] The demand for temperature control in outdoor sportswear is growing, and phase change materials (PCMs) are widely used in the production of temperature-controlled fabrics due to their heat storage and temperature regulation properties. While existing temperature-controlled fabrics possess basic temperature regulation capabilities, they exhibit failure modes when used in outdoor clothing: repeated friction from hiking backpack straps causes localized coating peeling; insufficient breathability leads to dampness and coldness after intense sweating during skiing; and rapid PCM loss during stain washing after hiking. These failures under the complex stresses of outdoor environments cannot be covered by ordinary household washability tests.

[0003] Currently, the coating method is mostly used to load PCM onto the fabric surface, but the following problems are common: First, there is a lack of strong chemical bond between the finishing agent and the fiber, and the PCM is easy to fall off after washing, making it difficult to achieve both long-term temperature control and water resistance; Second, in order to increase the load and adhesion, high solids content coatings or dense cross-linked networks are often used, which leads to the clogging of fabric pores and a significant decrease in breathability and wearing comfort; Third, in high-intensity outdoor use, the coating is prone to problems such as powdering, cracking and peeling under repeated bending and friction, and the temperature control function quickly fails.

[0004] Therefore, developing a temperature-controlled fabric that combines long-lasting temperature control, water resistance, and high outdoor durability, as well as its preparation method, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing temperature-controlled fabric and its application in outdoor clothing in order to solve the above-mentioned problems.

[0006] The present invention achieves the above objectives through the following technical solutions: A method for preparing a temperature-controlled fabric includes the following steps: (1) First, disperse the wetting and penetrating agent and PDA-CNT in water, then add SH-β-CD-PCM and waterborne polyurethane emulsion and mix, then add vinyl silane coupling agent, and finally add photoinitiator. Stir and disperse evenly, adjust the viscosity to 1000-2000 mPa·s, and prepare the finishing solution. (2) The base fabric is immersed in the finishing solution and subjected to a two-dip and two-roll process; (3) Pre-dry the treated base fabric to remove surface free water; (4) Perform UV crosslinking treatment on the pre-dried base fabric; (5) Pass the UV-crosslinked base fabric through saturated steam for steam-induced treatment, so that the coating can be further cured under humid and hot conditions; (6) The base fabric after steam induction treatment is dried, shaped, cooled and rolled up to obtain temperature control fabric.

[0007] As a further optimization of the above invention, the raw materials in the finishing liquid in step (1) are as follows by weight: 10-14 parts of SH-β-CD-PCM, 0.2-0.6 parts of PDA-CNT, 20-25 parts of waterborne polyurethane emulsion, 1.0-2.0 parts of vinyl silane coupling agent, 0.3-0.5 parts of photoinitiator, 0.2-0.4 parts of wetting and penetrating agent, 0.1-0.3 parts of thickener, 0.1-0.3 parts of pH buffer, and 1.0-2.0 parts of ethanol.

[0008] As a further optimization of the above invention, the rolling rate of the two-dip and two-roll process in step (2) is 60%-70%, and the machine speed is 10-15 m / min.

[0009] As a further optimization of the above invention, the pre-baking in step (3) is: hot air circulation pre-baking at 75-85℃ for 2-5 minutes.

[0010] As a further optimization of the above invention, the ultraviolet crosslinking treatment in step (4) is: wavelength 360-370nm, light intensity 80-100 mW / cm². 2 Irradiate at room temperature for 60-80 seconds.

[0011] As a further optimization of the above invention, the steam-induced treatment in step (5) is: introducing saturated steam at 85-95℃ for 60-100s.

[0012] As a further optimization of the above invention, the drying and shaping in step (6) is: hot air drying at 110-130℃ for 2-4 minutes; the winding tension of the cooling and winding is 0.4-1.0 N / cm.

[0013] A temperature-controlled fabric is prepared by the method described above.

[0014] The application of a temperature-controlled fabric in outdoor clothing, wherein the fabric has a phase change temperature of 25-28℃, a phase change enthalpy retention rate of ≥65% after 30 standard household washes, an abrasion resistance of ≥9800 cycles, and a peel strength of ≥1.0 N / cm.

[0015] The beneficial effects of this invention are as follows: This invention utilizes the synergistic effect of thiol-modified β-cyclodextrin-coated phase change material (SH-β-CD-PCM) and polydopamine-modified carbon nanotubes (PDA-CNT), combined with a dual-processing technique of UV-induced crosslinking to construct the coating's main network and saturated vapor-induced optimization of the coating's microstructure. This ensures the phase change material is firmly anchored to the coating network, significantly improving the fabric's washability, abrasion resistance, and coating stability during high-intensity outdoor use. The phase change enthalpy retention rate reaches 82.2% after 30 washes; simultaneously, peel strength and abrasion resistance are significantly improved, with an abrasion resistance of 12,500 cycles, effectively solving the problem of easy coating peeling and failure during high-intensity outdoor use. The temperature-controlled fabric produced by this invention possesses excellent properties of long-lasting temperature control, washability, and high-intensity outdoor durability, demonstrating significant industrialization value. Detailed Implementation

[0016] The present application will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.

[0017] Unless otherwise specified, all methods used in this invention are conventional methods known to those skilled in the art. Where specific conditions are not specified, they shall be performed according to conventional conditions or conditions recommended by the manufacturer. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0018] Example 1

[0019] 1. Preparation of finishing solution The raw materials for preparing the finishing solution, by weight, include: 12 parts of thiol-modified β-cyclodextrin-coated phase change material (SH-β-CD-PCM); 0.4 parts of polydopamine-modified carbon nanotubes (PDA-CNT); 24 parts of aqueous polyurethane emulsion; 1.5 parts of vinyl silane coupling agent; 0.4 parts of photoinitiator; 0.3 parts of wetting and penetrating agent; 0.2 parts of thickener; 0.2 parts of pH buffer (sodium acetate-acetic acid buffer system); and 1.5 parts of ethanol.

[0020] The preparation of SH-β-CD-PCM involved dispersing β-cyclodextrin in anhydrous ethanol, adding 3-mercaptopropionic acid, and esterifying the mixture at 65°C for 5 h in the presence of the catalyst p-toluenesulfonic acid and the dehydrating agent dicyclohexylcarbodiimide (DCC). After the reaction, the byproduct dicyclohexylurea (DCU) was removed by filtration, the solvent was removed by vacuum distillation of the filtrate, and the mixture was recrystallized from ethanol and dried under vacuum to obtain SH-β-CD. Using a melt adsorption method, SH-β-CD was mixed with molten paraffin (phase transition temperature 26°C) at a mass ratio of 1:1 and stirred under vacuum at 75°C for 2.5 h to allow paraffin molecules to enter the cyclodextrin cavity and form an inclusion complex. After cooling to room temperature, the mixture was ground and sieved to obtain SH-β-CD-PCM.

[0021] Preparation of PDA-CNTs: Multi-walled carbon nanotubes were dispersed in Tris-HCl buffer (pH 8.5), dopamine hydrochloride was added, and the mixture was stirred at room temperature for 24 h. After centrifugation, washing, and freeze-drying, PDA-CNTs were obtained. The polydopamine coating amount was controlled at 15-25 wt%.

[0022] Preparation method of finishing solution: Add an appropriate amount of deionized water to a stainless steel mixing tank, start stirring at 250 r / min, and add the following components in sequence: Add the wetting and penetrating agent, stir for 4 min until completely dissolved, and the solution is clear and transparent. Add polydopamine-modified carbon nanotubes (PDA-CNT), start a high-speed disperser at 7000 r / min, and disperse for 9 min. Let stand for 5 min to confirm that there is no sedimentation or agglomeration.

[0023] Add the thiol-modified β-cyclodextrin-coated phase change material (SH-β-CD-PCM), reduce the stirring speed to medium (450 r / min), and stir for 13 min to ensure thorough dispersion and a homogeneous mixture with PDA-CNT. Add the aqueous polyurethane emulsion and stir at medium speed for 8 min to ensure a homogeneous mixture with the functional dispersion.

[0024] In a separate container, dissolve the pH buffer in deionized water, add ethanol, stir until homogeneous, and adjust the pH to 5 with glacial acetic acid to prepare a silane pre-dispersion. Slowly add the vinylsilane coupling agent dropwise to this pre-dispersion and stir at room temperature for 13 minutes to obtain a clear and transparent silanol pre-hydrolyzed solution. Add the obtained silanol pre-hydrolyzed solution slowly to the mixed system over 10 minutes while maintaining a stirring speed of 450 r / min. After the addition is complete, continue stirring for 5 minutes.

[0025] Finally, add the photoinitiator and stir for 5 minutes in the dark. Add the remaining deionized water and thickener, stir for 13 minutes, and adjust the viscosity to 1500 mPa·s at 25°C.

[0026] Methods for preparing temperature-controlled fabrics Methods for preparing temperature-controlled fabrics: The polyester / nylon base fabric was treated with the finishing solution prepared above as follows: Prepare the finishing solution. Disperse SH-β-CD-PCM, PDA-CNT, vinyl silane coupling agent, photoinitiator, and waterborne polyurethane emulsion evenly in water, and adjust the viscosity to 1500 mPa·s to prepare the finishing solution.

[0027] The process involves two dips and two slits. The base fabric is sequentially passed through the first dip tank for 3 minutes, then through the first roller and the second dip tank for 3 minutes, and finally through the second roller for a two-dip and two-slit process. The liquid level is 65%, and the machine speed is 12 m / min.

[0028] Pre-drying. Pre-dry at 80℃ using hot air circulation for 3 minutes to remove free water from the surface of the base fabric.

[0029] UV crosslinking. A UV LED curing machine was used, with a wavelength of 365 nm and a light intensity of 90 mW / cm². 2 Irradiate for 70 seconds at room temperature.

[0030] Steam induction. The base fabric is placed in a steam oven and treated with 90°C saturated steam for 90 seconds.

[0031] Drying and shaping. Dry with hot air at 120℃ for 3 minutes.

[0032] Cooling and winding. The base fabric is cooled to room temperature using a circulating water cooling roller (roller surface temperature ≤30℃) and then wound up with a winding tension of 0.5 N / cm, resulting in a long-lasting temperature-controlled fabric that is washable, durable, and has high strength for outdoor use.

[0033] Example 2

[0034] The raw materials for preparing the finishing solution, by weight, include: 10 parts SH-β-CD-PCM, 0.2 parts PDA-CNT, 20 parts waterborne polyurethane emulsion, 1.0 part vinyl silane coupling agent, 0.3 parts photoinitiator, 0.2 parts wetting and penetrating agent, 0.1 parts thickener, and the balance being deionized water. The preparation process is completely consistent with Example 1.

[0035] Example 3

[0036] The raw materials for preparing the finishing solution, by weight, include: 14 parts SH-β-CD-PCM, 0.6 parts PDA-CNT, 25 parts waterborne polyurethane emulsion, 2.0 parts vinyl silane coupling agent, 0.5 parts photoinitiator, 0.4 parts wetting and penetrating agent, 0.3 parts thickener, and the balance being deionized water. The preparation process is completely consistent with Example 1.

[0037] Comparative Example 1 Compared with Example 1, the difference is that vinyl silane coupling agent (KH-171) is not added in the preparation of the finishing solution, while the other components and weight parts are the same as in Example 1.

[0038] The preparation method is as follows: Finishing solution preparation: The finishing solution was prepared according to the method in Example 1, the only difference being the omission of the step of adding the vinyl silane coupling agent. Temperature-controlled fabric preparation: The polyester / nylon base fabric was subjected to two dips and two nips, pre-drying, UV crosslinking, saturated steam induction treatment, drying and setting, and cooling and winding according to the method in Example 1. The process parameters for each step were the same as in Example 1.

[0039] Comparative Example 2 Compared with Example 1, the difference is that no photoinitiator is added in the preparation of the finishing solution, while the other components and their weight proportions are the same as in Example 1.

[0040] The preparation method is as follows: the finishing solution is prepared according to the method of Example 1, the only difference being that the step of adding the photoinitiator is omitted. In the preparation of temperature-controlled fabric, the treatment method of step (4) is adjusted to: replacing ultraviolet crosslinking with 80°C hot air baking for 30 seconds, and the remaining steps and process parameters are the same as in Example 1.

[0041] Comparative Example 3 Compared with Example 1, the difference is that the thiol-modified β-cyclodextrin-coated phase change material (SH-β-CD-PCM) was replaced with an equal amount of ordinary melamine resin wall microcapsule phase change material, while the remaining components and weight proportions were the same as in Example 1. The preparation method was as follows: The finishing solution was prepared according to the method of Example 1, with the only difference being the use of ordinary melamine resin wall microcapsule PCM instead of SH-β-CD-PCM.

[0042] Temperature-controlled fabric preparation: All preparation steps and process parameters are the same as in Example 1.

[0043] Comparative Example 4 Compared to Example 1, the difference is that polydopamine-modified carbon nanotubes (PDA-CNTs) are not added in the finishing solution preparation; all other components and weight proportions are the same as in Example 1. The preparation method is as follows: Finishing solution preparation: The finishing solution is prepared according to the method of Example 1, with the only difference being the omission of the PDA-CNT addition step. Temperature-controlled fabric preparation: All preparation steps and process parameters are the same as in Example 1.

[0044] Comparative Example 5 The raw material composition is exactly the same as in Example 1. The preparation method is as follows: the difference from Example 1 is that step (5) saturated steam induction treatment is omitted, that is, after the ultraviolet crosslinking is completed, step (6) drying and shaping (120℃ hot air drying for 3 min) is directly carried out. The remaining steps and process parameters are the same as in Example 1.

[0045] Comparative Example 6 The raw material composition is exactly the same as in Example 1. The preparation method is as follows: The difference from Example 1 is that step (4) UV crosslinking and step (5) saturated steam induction treatment are omitted and replaced by a traditional one-step hot drying process. Specifically, after the pre-drying in step (3) is completed, it is directly put into the drying oven and dried with hot air at 105°C for 5 minutes, followed by step (6) cooling and winding. The remaining steps and process parameters are the same as in Example 1.

[0046] Performance testing 1. Phase transition enthalpy test Differential scanning calorimetry (DSC) was used. Approximately 5-10 mg of sample was cut from the fabric to be tested and placed in a sealed aluminum crucible. The test temperature range was set to the phase transition temperature, with a heating / cooling rate of 10 °C / min, under a nitrogen protective atmosphere and a flow rate of 50 mL / min. The melting peak during the heating process was recorded, and the enthalpy of phase transition per unit mass of fabric (J / g) was calculated by integrating the peak area. Each sample was tested in triplicate, and the arithmetic mean was taken as the test result.

[0047] Table 1. Phase change enthalpy test results for different temperature-controlled fabrics.

[0048] As shown in Table 1, the initial phase change temperature of the temperature-controlled fabrics prepared in each embodiment and comparative example is stable in the range of 26.1~27.0℃, which is basically consistent with the nominal phase change temperature (26℃) of the selected phase change material, indicating that the finishing process did not have a significant impact on the thermodynamic properties of the phase change material.

[0049] Examples 1-3 show that as the amount of SH-β-CD-PCM in the finishing solution increases from 10 parts to 12 parts and then to 14 parts, the phase change enthalpy of the resulting fabric increases from 15.2 J / g to 18.5 J / g and then to 20.1 J / g. This indicates that the heat storage capacity of the fabric can be controlled by adjusting the content of phase change material in the formula.

[0050] The initial phase transition enthalpy of each comparative example was 17.5~18.3 J / g, which was basically equivalent to that of Example 1, with no significant difference. This indicates that regardless of whether vinylsilane coupling agent, photoinitiator, PDA-CNT, or key steps such as steam treatment and UV crosslinking are added, the initial phase change material loading in the finishing process can reach a similar level. Therefore, the initial phase transition enthalpy is not a key indicator distinguishing this invention from the comparative examples.

[0051] 2. Phase change enthalpy retention rate test after water washing Tests were conducted according to GB / T 8629-2017 "Home Washing and Drying Procedures for Textile Testing" and GB / T 43820-2024 "Determination of Heat Storage and Release Properties of Textiles Containing Phase Change Materials". The phase change enthalpy before and after washing was recorded, and the retention rate was calculated. A standard type A washing machine was used, with washing program 4N, washing temperature 40℃, low water level, washing time 12 min, rinsing 3 times, and spin-drying speed 500 r / min. The total washing load was 2.0 kg, supplemented with polyester fiber admixtures. 30 washing cycles were performed, followed by hanging drying (program A). 5-10 mg samples were cut from the fabric before and after washing and placed in a sealed aluminum crucible. Differential scanning calorimetry (DSC) was used under a nitrogen atmosphere (50 mL / min), with the temperature increased from 5℃ to 45℃ at a rate of 10℃ / min. The melting curve was recorded, and the phase change enthalpy (J / g) was calculated by integration. Three parallel samples were tested for each sample, and the average value was taken. Calculate using the following formula: Phase change enthalpy retention rate (%) = H n / H0×100% Where H n Let H0 be the phase transition enthalpy (J / g) of the sample after n water washes, and H0 be the initial phase transition enthalpy (J / g) of the unwashed sample. Calculate the retention rates after unwashed and 30 water washes respectively.

[0052] Table 2. Test results of phase change enthalpy retention rate of different temperature-controlled fabrics

[0053] As shown in Table 2, after 30 standard household water washes, the phase change enthalpy retention rates of the various examples and the comparative examples showed significant differences.

[0054] The phase transition enthalpy retention rates after 30 water washes in Examples 1-3 were 68.0%–82.2%, significantly higher than those in Comparative Examples 1-3 and Comparative Example 6. The phase transition enthalpy retention rates after 30 water washes in Comparative Examples 1, 2, and 3 were 25.3%, 27.8%, and 25.1%, respectively, all below 30%, and there was no significant difference among the three. These results indicate that the vinyl silane coupling agent, photoinitiator, and thiol modification of SH-β-CD-PCM are all indispensable and together constitute the basis of the coating. Comparative Example 2, using a traditional thermosetting process, could not achieve crosslinking, and its retention rate was at the same low level as Comparative Examples 1 and 3, proving that simple thermosetting cannot replace UV crosslinking. Comparative Example 6, using a traditional one-step thermal drying process, had a retention rate of only 18.0%, the lowest among all samples; Comparative Example 5, skipping steam treatment, had a retention rate of 67.8%, lower than that of Examples 1-3. Comparative Example 4 showed a retention rate of 72.1%, which is close to that of Example 1, indicating that PDA-CNT has no significant negative impact on the wash resistance of PCM. Example 1 achieved a phase change enthalpy retention rate of 82.2% after 30 washes, the highest among all samples, indicating that its formulation is the optimal fabric.

[0055] 3. Air permeability test The test was conducted according to GB / T 5453-2025 "Textiles - Determination of Air Permeability of Fabrics". A digital fabric air permeability meter was used, with a test area of ​​20 cm². 2 The test pressure difference was 100 Pa. After conditioning the sample under standard atmospheric conditions (20℃, 65% RH) for 24 hours, it was flattened and fixed on the sample platform. The suction fan was turned on to allow air to pass through the sample, and the flow rate was adjusted until the pressure difference stabilized at 100 Pa. The airflow rate was recorded. Ten different locations were tested for each sample, and the air permeability was calculated using the following formula: R=q v / A×167, where R is the air permeability (mm / s), q v The average gas flow rate is (L / min), and A is the test area (20 cm²). 2 The arithmetic mean was calculated as the test result. Air permeability loss rate = (Air permeability of blank base fabric - Air permeability of sample) / Air permeability of blank base fabric × 100%.

[0056] Table 3. Test results of air permeability of different temperature-controlled fabrics

[0057] The air permeability of the blank sample was 850 mm / s. The air permeability of Examples 1-3 was 790~820 mm / s, with an air permeability loss rate of only 1.8%~8.2%, indicating that the finishing process of this invention has minimal impact on the original air permeability of the base fabric. The air permeability of Comparative Examples 1-3 was 800~810 mm / s, with a loss rate of 4.7%~5.9%, close to that of Examples 1-3, indicating that the reaction itself has no significant negative impact on air permeability. The air permeability of Comparative Example 4 was 780 mm / s, with a loss rate of 8.2%, at the same level as Examples 1-3, indicating that PDA-CNT, within the limited dosage range (0.2-0.6 parts), will not significantly clog the fabric pores. The air permeability of Comparative Example 5 was 510 mm / s, with a loss rate of 40.0%; the air permeability of Comparative Example 6 was 480 mm / s, with a loss rate of 43.5%. Both were significantly lower than those of Examples 1-3, indicating that the steam treatment step and UV crosslinking pre-conversion play a crucial role in inhibiting coating clogging and maintaining fabric air permeability. Comparative Example 6, while retaining PDA-CNT, lacked the UV crosslinking pre-setting step. The coating exhibited higher fluidity during drying at 105°C, and pore blockage was more severe than in Comparative Example 5. This data conversely demonstrates the "pore-preserving" effect of UV crosslinking. Example 1, with an air permeability of 820 mm / s and a loss rate of 3.5%, demonstrated the best overall washability, peel strength, and abrasion resistance, thus being determined as the optimal fabric.

[0058] 4. Peel strength test The test was conducted according to GB / T 2792-2014, "Test Method for Peel Strength of Pressure-Sensitive Adhesive Tapes". Three samples, each measuring 200 mm × 50 mm, were cut from the fabric to be tested. The original sample and the sample after 30 washes were tested separately. The peel angle was 180°, the peel speed was 100 mm / min, and the effective peel length was ≥100 mm. The sample was laid flat with the coated side down, and approximately 20 mm of the coated side was manually peeled off. The peeled end was clamped in the upper clamp, and the base fabric was clamped in the lower clamp, ensuring a 180° peel angle. Peeling was performed at a uniform speed of 100 mm / min, and the average peel force (N) of the stable section was recorded. Peel strength (N / cm) = Average peel force (N) / Sample width (cm) Three samples were tested for each sample, and the arithmetic mean was taken.

[0059] Table 4. Peel strength test results of different temperature-controlled fabrics

[0060] Table 4 shows that the original peel strength of Examples 1-3 was 1.5–2.0 N / cm, and after 30 washes, it was 1.1–1.6 N / cm, with a retention rate of 73.3%–83.3%, significantly higher than Comparative Examples 1-3 and Comparative Example 6. The retention rates of Comparative Examples 1, 2, and 3 after washing were all below 45%, indicating that the lack of any element—vinylsilane coupling agent, photoinitiator, or thiol modification of SH-β-CD-PCM—caused a sharp decline in coating adhesion. Comparative Example 6, using conventional one-step heat drying, had an original peel strength of 0.6 N / cm and a retention rate of 0.2 N / cm after 30 washes, the lowest among all samples, indicating that the conventional process could not form an effective adhesion network. Comparative Example 4 had an original peel strength of 1.6 N / cm and a retention rate of 1.2 N / cm after 30 washes, with a retention rate of 75.0%, close to that of Examples 1-3, indicating that PDA-CNT had no significant negative impact on peel strength. Comparative Example 5 showed an original peel strength of 1.4 N / cm and a peel strength of 0.9 N / cm after 30 water washes, with a retention rate of 64.3%, which was lower than that of Examples 1-3. This indicates that the steam treatment step has a positive effect on the long-term maintenance of coating adhesion.

[0061] Example 1: The original peel strength was 1.8 N / cm, and after 30 washes it was 1.5 N / cm, with a retention rate of 83.3%, which was the highest among all samples. It had the best overall washability, peel strength and abrasion resistance, making it the best fabric.

[0062] Thermal resistance and moisture resistance testing The test was conducted according to GB / T 11048-2018 "Determination of thermal and moisture resistance of textiles under steady-state conditions for physiological comfort". Three samples were cut, each with a size ≥300 mm × 300 mm, and conditioned for 24 hours under standard atmospheric conditions. The test plate temperature was 35℃, the ambient temperature was 20℃, the relative humidity was 65%, and the airflow velocity was ≤1 m / s.

[0063] The sample was placed on a dry test plate. After the temperature stabilized, the power required to maintain the test plate at a constant temperature was measured, and the thermal resistance R was calculated. ct (m) 2 • K / W). Moisture resistance test: The test plate surface is covered with a standard thin film and saturated with water. The sample is then covered, and the power is measured after steady state. The moisture resistance Ret (m) is calculated. 2 ·Pa / W). Moisture permeability index = R ct / (0.0162 * Ret), The closer the moisture permeability index is to 1, the better the thermal and moisture comfort. Three samples were tested for each sample, and the arithmetic mean was taken.

[0064] Table 5. Test results of thermal resistance and moisture resistance of different temperature-controlled fabrics

[0065] As shown in Table 5, the moisture permeability index of Examples 1-3 ranged from 0.31 to 0.43. Comparative Example 4 had a moisture permeability index of 0.32, which was at the same level as Examples 1-3, indicating that PDA-CNT had no significant negative impact on moisture permeability within the specified dosage range. Comparative Examples 1-3 had moisture permeability indices of 0.24-0.27, significantly lower than Examples 1-3 and Comparative Example 4, indicating that the cross-linked network formed by the reaction was key to improving thermal and moisture comfort. Comparative Example 5 had a moisture permeability index of 0.30, lower than Examples 1-3, indicating that the steam treatment step had a positive effect on optimizing the coating microstructure and improving moisture permeability. Comparative Example 6 had a moisture permeability index of 0.22, the lowest among all samples, indicating that the dense coating formed by the traditional one-step heat drying process severely hindered the transfer of moisture and heat. Example 3 had a moisture permeability index of 0.43, the highest among all samples; Example 1 had a moisture permeability index of 0.38, close to Example 3, and exhibited the best overall wash resistance and peel strength, making it the best fabric.

[0066] Abrasion resistance test The test was conducted according to GB / T 21196.2-2007, "Textiles - Martindale Method: Determination of Abrasion Resistance of Fabrics - Part 2: Determination of Specimen Breakage". At least three circular specimens, approximately 38 mm in diameter, were cut from the fabric to be tested. The specimens should include different warp and weft directions, avoiding selvage and obvious defects. The specimens were conditioned for at least 8 hours under standard atmospheric conditions (temperature 20°C, relative humidity 65%). The specimens were fixed flat in the specimen holder, with the coated side facing outwards as the abrasion surface. The abrasive (No. 600 wet sandpaper) was fixed on the grinding table. A friction load was applied, ensuring close contact between the specimen and the abrasive. The instrument was started, and the specimen rubbed against the abrasive in a Lissajous pattern. The abrasion resistance was periodically checked for coating wear, observing for any breakage. The total number of friction cycles at which the coating broke was recorded. Specimen breakage is defined as the coating of the coated fabric being damaged to the point of exposing the base fabric or having flaky coating peeling off. The number of friction cycles at which each specimen broke represents the abrasion resistance performance, and the arithmetic mean of the three specimens was taken as the test result. A higher number of wear resistance cycles indicates better wear resistance of the coating.

[0067] Table 6. Abrasion resistance test results of different temperature-controlled fabrics

[0068] As shown in Table 6, the abrasion resistance of Examples 1-3 ranged from 9800 to 13200 cycles, significantly higher than that of Comparative Examples 1-3 and Comparative Example 6. Comparative Examples 1, 2, and 3 all had abrasion resistance below 5000 cycles, indicating a lack of any of the following elements: vinyl silane coupling agent, photoinitiator, or thiol modification of SH-β-CD-PCM. This resulted in insufficient adhesion between the coating and the fiber, making it prone to wear and detachment. Comparative Example 6, using a conventional one-step thermal drying process, had the lowest abrasion resistance at 3200 cycles, indicating the worst adhesion of the coating formed by the conventional process, making it prone to failure under high-intensity outdoor use.

[0069] Comparative Example 4 achieved 9500 abrasion cycles, similar to Example 2 but significantly lower than Examples 1 and 3. This result indicates that PDA-CNT has a certain enhancing effect on abrasion resistance, but it needs to be combined with steam treatment to achieve the best effect. Comparative Example 5 achieved 7600 abrasion cycles, lower than Comparative Example 4, further demonstrating the improving effect of steam treatment on coating toughness and abrasion resistance. Example 1 achieved 12500 abrasion cycles, exhibiting the best overall wash resistance, peel strength, and abrasion resistance, making it the optimal fabric.

[0070] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.

Claims

1. A method for preparing a temperature-controlled fabric, characterized in that, Includes the following steps: First, disperse the wetting and penetrating agent and PDA-CNT in water, then add SH-β-CD-PCM and waterborne polyurethane emulsion and mix, then add vinyl silane coupling agent, and finally add photoinitiator. Stir and disperse evenly, adjust the viscosity to 1000-2000 mPa·s, and prepare the finishing solution. The base fabric is immersed in the finishing solution and subjected to a two-dip and two-roll process. The treated base fabric is pre-dried to remove surface free water; The pre-dried base fabric is subjected to ultraviolet crosslinking treatment; The UV-crosslinked base fabric is passed through saturated steam for steam-induced treatment, so that the coating is further cured under humid and hot conditions. The base fabric after steam-induced treatment is dried, shaped, cooled, and rolled up to obtain the temperature-controlled fabric.

2. The method for preparing temperature-controlled fabric according to claim 1, characterized in that, The raw materials for preparing the finishing solution in step (1) include, by weight: 10-14 parts of SH-β-CD-PCM, 0.2-0.6 parts of PDA-CNT, 20-25 parts of waterborne polyurethane emulsion, 1.0-2.0 parts of vinyl silane coupling agent, 0.3-0.5 parts of photoinitiator, 0.2-0.4 parts of wetting and penetrating agent, 0.1-0.3 parts of thickener, 0.1-0.3 parts of pH buffer, and 1.0-2.0 parts of ethanol.

3. The method for preparing temperature-controlled fabric according to claim 1, characterized in that, In step (2), the slurry rate of the two-dip and two-roll process is 60%-70%, and the machine speed is 10-15 m / min.

4. The method for preparing temperature-controlled fabric according to claim 1, characterized in that, The pre-baking in step (3) is: 75-85℃ hot air circulation pre-baking for 2-5 minutes.

5. The method for preparing temperature-controlled fabric according to claim 1, characterized in that, The ultraviolet crosslinking treatment in step (4) is performed with a wavelength of 360-370 nm and a light intensity of 80-100 mW / cm. 2 Irradiate at room temperature for 60-80 seconds.

6. The method for preparing temperature-controlled fabric according to claim 1, characterized in that, The steam-induced treatment in step (5) is: introducing saturated steam at 85-95℃ for 60-100s.

7. The method for preparing temperature-controlled fabric according to claim 1, characterized in that, The drying and shaping in step (6) is as follows: hot air drying at 110-130℃ for 2-4 minutes; the winding tension of the cooling and winding is 0.4-1.0 N / cm.

8. A temperature-controlled fabric, characterized in that, It is prepared by any one of the preparation methods described in claims 1-7.

9. An application of the temperature-controlled fabric as described in claim 8 in outdoor clothing, characterized in that, The fabric has a phase change temperature of 25-28℃, a phase change enthalpy retention rate of ≥65% after 30 standard household washes, an abrasion resistance of ≥9800 cycles, and a peel strength of ≥1.0 N / cm.